2019
DOI: 10.1002/jcu.22683
|View full text |Cite
|
Sign up to set email alerts
|

Presence of fragmented QRS is associated with increased epicardial adipose tissue thickness in hypertensive patients

Abstract: Background Epicardial adipose tissue (EAT) is a cardiometabolic risk factor, and its possible relationship with hypertension has been reported previously. Fragmented QRS (fQRS) detected on electrocardiography (ECG) has been demonstrated to be a marker of myocardial fibrosis. In this study, we aimed to investigate the relationship between the thickness of EAT, and presence of fQRS in hypertensive patients. Methods Consecutive patients who were diagnosed with hypertension were included in the study. ECG and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Cardiac fibrosis is a well-known underlying mechanism of occurrence of fQRS in various cardiac pathologies. Bekar et al (28) showed fQRS as an independent predictor of EAT in hypertensive patients in their recent study. Yaman et al (11) showed that the presence of fQRS was associated with increased EAT in a healthy population.…”
Section: Discussionmentioning
confidence: 93%
“…Cardiac fibrosis is a well-known underlying mechanism of occurrence of fQRS in various cardiac pathologies. Bekar et al (28) showed fQRS as an independent predictor of EAT in hypertensive patients in their recent study. Yaman et al (11) showed that the presence of fQRS was associated with increased EAT in a healthy population.…”
Section: Discussionmentioning
confidence: 93%
“…Myocardial fibrosis is a well-known underlying mechanism of fQRS occurrence in various cardiac pathologies 13 . Bekar et al demonstrated fQRS as an independent predictor of EFT in hypertensive patients in their recent study 22 . Yaman et al showed that the presence of fQRS was associated with increased EFT in healthy population 23 .…”
Section: Discussionmentioning
confidence: 95%
“…The present study aimed to evaluate the frequency of nQRS complexes and fQRS observed on ECG in dogs with naturally occurring MMVD and to assess the association between these electrocardiographic changes and disease severity. In human medicine, the presence of fQRS was associated with various cardiac conditions such as myocardial dysfunction, ischemic and non-ischemic cardiomyopathy, pulmonary hypertension, mitral valve stenosis, atrial septal defect, hypertrophic obstructive cardiomyopathy or Brugada syndrome (Heller et al 1996 ; Morita et al 2008 ; Das et al 2010 ; Yuce et al 2010 ; Bekar et al 2019 ; Bi et al 2020 ), therefore the presence of fQRS in ECG is accepted in human medicine as a marker of myocardial scar or fibrosis (Das et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of these changes with the disease severity has not been investigated yet [3]. In human medicine, notching of the QRS complex has been studied in various cardiovascular diseases being associated with worse prognosis [4][5][6][7][8][9][10]. It was suggested that the alteration in QRS morphology is related to regional myocardial scar, leading to a conduction delay or a fragmentation of QRS complexes [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation